Biopolymers Applied to Remove Metal Ions Through Ultrafiltration. a Review - Sanchez-Poblete, J (Sociedad Chilena de Quimica, 2020)
This manuscript is an overview of the versatile biopolymer materials alginic acid, carboxymethyl cellulose, and quaternized chitosan which contain different functional groups to remove hazardous inorganic species. These bioadsorbents are completely water-soluble and have a high versatility to achieve a higher sorption capacity and efficiency under different experimental conditions in combination with ultrafiltration membranes through the liquid-phase polymer-based retention (LPR) technique. In general, thesebioadsorbents are friendly with the environment and have a higher biodegradability compared with those more employed synthetic polymers. © 2020 Sociedad Chilena de Quimica. All rights reserved.